Mainstreaming the Northeast in India's Look and Act East Policy (Springer Singapore, 2018)
This book provides a detailed account of the evolution of India's Look and Act East Policy, addressing the nuances of the policy and its efficacy for the Northeast Region. The Northeastern India as a region is landlocked, sharing most of its boundary with neighbouring countries of South and South East Asia. It empirically explores the progress in and prospects for trade, investment and connectivity between Northeast India and Southeast Asian countries. Further, it discusses a range of regional and sub-regional multilateral initiatives - e.g. the Bay of Bengal Initiative for Multi-Sectoral Technical and Economic Cooperation (BIMSTEC), Bangladesh-China-India-Myanmar (BCIM), and Mekong-Ganga Cooperation (MGC) - that could potentially strengthen the cooperation between Northeast India and neighboring regions in the social, cultural and economic spheres.